A password authentication method for remote users based on smart card and biometrics. (3rd April 2017) - Om, Hari; Banerjee, Subhasish
Abstract: Das has improved the biometric-based remote user authentication using smart card [13]. This scheme is based on biometric, password, and the random nonce generated by the user and the server. It is very efficient as far as the computational cost is concerned. This scheme however has some security weaknesses such as replay and offline password guessing attacks. In this paper, we present a review of the Das's scheme and discuss its weaknesses. In this paper, we develop a new scheme that overcomes all its weaknesses.